Surface and Wear Analysis of Zinc Phosphate Coated Engine Oil Ring and Cylinder Liner Tested with Commercial Lubricant - Ozkan, Dogus; Kaleli, Hakan (SAGE PUBLICATIONS LTD, 2014)
The objective of this study was to evaluate the tribological performance through investigating protective additive layer and friction coefficient and implementing the quantitative wear measurements on the rubbed surface of the sliding pairs. The specimens of oil ring were rubbed against cast iron engine cylinder liner under boundary lubrication conditions. The ring and liner surfaces were examined by optical, scanning electron microscope and atomic force microscopy. The elemental analysis of surfaces was performed by using energy dispersive X-ray spectroscopy. Surface observations showed that coating was removed from the ring surface. Higher levels of Ca, Zn, P, and S elemental ratios (0.93%, 0.45%, 1.55%, and 1.60% as atomic percent) were detected on the cylinder liner surface. Wear width, length, and depth measurements were performed by optical and atomic force microscopies on the ring and cylinder liner surface. The results showed that wear widths for oil ring were 1.59 mu m and 1.65 mu m; wear widths for cylinder liner were 3.20 mu m and 3.18 mu m; wear depths for oil ring were 100 nm; and wear depths for cylinder liner were 482 nm. Wear data were taken mostly from the additive layer points detected by SEM and X-ray measurements.
Keywords: PISTON-RING; FRICTION; COATINGS; MODEL; AFM; Thermodynamics; Engineering